2007
DOI: 10.1021/jo070681h
|View full text |Cite
|
Sign up to set email alerts
|

Et2Zn-Catalyzed Intramolecular Hydroamination of Alkynyl Sulfonamides and the Related Tandem Cyclization/Addition Reaction

Abstract: Intramolecular hydroamination of alkynyl amides was effected by a catalytic amount of Et2Zn (20 mol %) to form indole derivatives, and a tandem cyclization/nucleophilic addition procedure involving reaction of the indole zinc salt intermediate with acid chlorides or halides was developed to provide an efficient approach to C3-substituted indole derivatives when an excess of Et2Zn (120 mol %) was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(59 citation statements)
references
References 48 publications
1
57
0
1
Order By: Relevance
“…Analogous Et 2 Zn-mediated approach for an efficient synthesis of 3-bromo-and -acylindoles was reported by Zhao and coworkers [209,210]. In addition, the same authors demonstrated that catalytic amounts of diethylzinc could promote a common 5-endo-dig cyclization of N-sulfonylated ortho-alkynylanilines, affording C3-unfunctionalized indoles in good to excellent yields.…”
Section: Synthesis Of Indoles Via Cycloisomerization Reactionsmentioning
confidence: 88%
“…Analogous Et 2 Zn-mediated approach for an efficient synthesis of 3-bromo-and -acylindoles was reported by Zhao and coworkers [209,210]. In addition, the same authors demonstrated that catalytic amounts of diethylzinc could promote a common 5-endo-dig cyclization of N-sulfonylated ortho-alkynylanilines, affording C3-unfunctionalized indoles in good to excellent yields.…”
Section: Synthesis Of Indoles Via Cycloisomerization Reactionsmentioning
confidence: 88%
“…[18][19][20][21] By taking the intermediate B formed from the cyclic anti-azametallation of alkynes as the starting point, its reaction with CO 2 under the reported protocols for the indole synthesis from 2-alkynylanilines was attempted (Table 1, entries 1-4). [18][19][20][21] Unfortunately, no indolecarboxylic acid 2a was formed indicating the low reactivity of intermediate C (M = Rh, Hg) towards CO 2 . It is surprising that no carboxylation occurred even with CuA C H T U N G T R E N N U N G (OAc) 2 [21] although the are many reports on Cu-catalyzed CO 2 -based carboxylation reaction!…”
Section: Introductionmentioning
confidence: 99%
“…2-Alkynylanilines with a ketonic carbonyl group in R 1 (entry 6), halogen (entries 11, 12, and 14) and ester (entry 13) functionality in R 2 or R 3 of the aryl group could also work very well in this reaction, leaving further opportunity for elaboration without protection and deprotection. The reaction can be conducted using 3 mmol (1.1 g) of 1h to produce 2h in toluene reflux 0 53 [18] 2 [c,d] Rh toluene 100 0 92 [19] 3 [d] HgA…”
Section: Introductionmentioning
confidence: 99%
“…These are usually sufficiently electrophilic for nucleophilic attack by water [2], alcohol [3,4], phenols [5], amines [6,7] and many other nucleophiles. A wide variety of transition metal based catalysts have been reported to catalyze alkyne hydration [8], alkynylaryl amine [9][10][11][12][13][14][15] and -phenol [16][17][18][19] cyclization, etc. However, there has not been any report, to the best of our knowledge, of one catalyst capable of carrying out cyclization and hydration in the same reaction flask.…”
Section: Introductionmentioning
confidence: 99%